Prima facie : a novel - Miller, Suzie (Henry Holt and Company, 2024)
"An adaptation of the Olivier Award-winning play that the New York Times wrote radiated with "visceral power," Suzie Miller's legal thriller Prima Facie is a heartbreaking, nuanced look at the system's flaws when protecting sexual assault and rape survivors, through the eyes of a star defense attorney"--